1997
DOI: 10.2165/00003088-199733060-00004
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors and CNS Drug Interactions

Abstract: The potential for drug-drug interactions in psychiatric patients is very high as combination psychopharmacotherapy used to treat comorbid psychiatric disorders, to treat the adverse effects of a medication, to augment a medication effect or to treat concomitant medical illnesses. Interactions can be pharmacodynamic or pharmacokinetic in nature. This paper focuses on the metabolic kinetic interactions between selective serotonin reuptake inhibitors (SSRIs) and other central nervous system (CNS) drugs. The evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(76 citation statements)
references
References 84 publications
3
66
0
7
Order By: Relevance
“…There is no evidence that Baclofen or Atenolol can increase Carbamazepine blood concentration. Fluvoxamine can do it, 16 but it did not cause Carbamazepine toxicity in this patient during the previous 2 years, and signs of Carbamazepine overdose were evident after Fluvoxamine was stopped. Therefore, Fluvoxamine is unlikely to have participated in the intoxication.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…There is no evidence that Baclofen or Atenolol can increase Carbamazepine blood concentration. Fluvoxamine can do it, 16 but it did not cause Carbamazepine toxicity in this patient during the previous 2 years, and signs of Carbamazepine overdose were evident after Fluvoxamine was stopped. Therefore, Fluvoxamine is unlikely to have participated in the intoxication.…”
Section: Discussionmentioning
confidence: 58%
“…It is eliminated through the hepatic pathway and catalyzed by cytochrome P450 (CYP3A subfamily), 13 so drugs that inhibit the activity of this cytochrome may elevate Carbamazepine blood level and cause toxicity. 11 These drugs include itriconazole, ketokonazole, clarythromycin, erythromycin, nefazodone, ritonavir, 14 isoniazide, propoxyphene, cimetidine, 15 fluvoxamine, fluoxetine, 16 and acetazolamide. 17 Here we present a case of Carbamazepine toxicity related to a pharmacokinetic interaction with either Oxybutynin or Dantrolene.…”
Section: Introductionmentioning
confidence: 99%
“…Fluvoxamine is a well-known to be a potent inhibitor of CYP1A2, 2C19 and 3A4. 20) Recently, Sugahara et al have recently reported that the concentration of alprazolam in non-smokers was increased by fluvoxamine, while that in smorkers was unchanged. 21) Thus, it is plausible that the extent of drug interactions by fluvoxamine may be affected by smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoxetine's metabolism involves the Cytochrome P450 system (Figure 1), and a combination of drugs which are also metabolised by CYPs may lead to drug interactions, even if fluoxetine has been discontinued for 4-5 weeks [55,[57][58][59][60][61].…”
Section: Fluoxetinementioning
confidence: 99%